2015
DOI: 10.1177/2165079914565348
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Nurses in Emergency Departments in Jordan

Abstract: Violence against nurses in emergency departments (EDs) has become a widespread phenomenon affecting nurses' job satisfaction and work performance. Literature is scarce regarding prevalence rates and causes of violence directed toward nurses in Jordan. The present study investigated violence experienced by Jordanian nurses in EDs and causes of violence from their perspectives. This descriptive study collected data from 174 Jordanian ED nurses. The majority of the participants (91.4%) reported experiencing viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 14 publications
9
58
0
11
Order By: Relevance
“…There was broad geographical variation in the primary studies: 13 were conducted in Australia, three were from the USA, three from the UK, and a study each from Canada, Cyprus, Italy, Jordan, Lebanon, Morocco, Nigeria, Palestine, Singapore, and Taiwan . Twenty‐seven (93%) studies scored 50–100% in the mixed methods appraisal tool indicating moderate to high quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was broad geographical variation in the primary studies: 13 were conducted in Australia, three were from the USA, three from the UK, and a study each from Canada, Cyprus, Italy, Jordan, Lebanon, Morocco, Nigeria, Palestine, Singapore, and Taiwan . Twenty‐seven (93%) studies scored 50–100% in the mixed methods appraisal tool indicating moderate to high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Harmful physical contact can include (but not limited to) striking, slapping, punching, spitting, kicking, choking, biting, pushing, sexual assault and use of weapons against staff. Verbal abuse can include (but not limited to) yelling, insults, intimidation, threats, bullying, harassment, use of derogatory gestures and swearing …”
Section: Resultsmentioning
confidence: 99%
“…16,18,19,[24][25][26] This difference may be due to cultural differences and the way in which violence is described. Similar findings were showed in Ghana.…”
Section: Resultsmentioning
confidence: 99%
“…26,29,30,39 Our study observed that the respondents perceive that the intense workload, high patient expectation and substance abuse were the important contributing factors to the violence against the health care workers similar to the study conducted in Jordan by Darawad et al in 2015 while some other studies have found factors like Direct contact of HCW with highly stressed patients and families because of illness, unrestricted movements of visitors in the hospitals, overcrowding, lack of staff training in prevention and management of aggression and violence, unsatisfied treatment plan, low staffing level, prevalence of weapons among patients/relatives, communication gap, long waiting periods as some of the contributing factors towards the high prevalence of workplace violence in healthcare settings. 26,33,[35][36][37][40][41][42][43] Ever reporting of violence was observed to be very high and encouraging in the current study but more research is required to find out the prevalence of regular reporting of such incidents as the studies globally have shown that only a fraction of these matters are reported. 26,28,29,[44][45][46] The current study indicated that the approx.…”
Section: Discussionmentioning
confidence: 99%